On the identity of the poorly known pea crab, Pinnothera obesa Dana, 1852, and description of a new species of Arcotheres Manning, 1993 from the Southwest Pacific (Decapoda: Brachyura: Pinnotheridae) - Komai, Tomoyuki; Kawai, Kei; Ng, Peter K.l. (Zootaxa, 2020)
The pinnotherid crab, Pinnothera obesa Dana, 1852, was originally described on the basis of material from Fiji, but its taxonomic status has long been obscure because the original description and figures are too brief and schematic by modern standards and the types are also lost. Examination of newly collected material from Fiji revealed the presence of two intertidal pinnotherid species assignable to the genus Arcotheres Manning, 1993, one of which is herein identified with Dana’s taxon. A neotype is designated for Arcotheres obesus n. comb. in the interest of nomenclatural stability, and a detailed redescription is given. Arcotheres obesus is morphologically similar to A. exiguus (Bürger, 1895) and A. rotundatus (Bürger, 1895), and differentiating characters are discussed. The species is also reported from Peninsular Malaysia. The second species is new to science, here described as Arcotheres ocularius, and is most similar to A. palaensis (Bürger, 1895) and A. arcophilus (Bürger, 1895). The new species is also recorded from Lombok, Indonesia. Arcotheres obesus and A. ocularius n. sp. are associated with bivalve mollusks of the genera Gafrarium spp. (Veneridae) and Anadara spp. (Arcidae), respectively.